Quality control in resting-state fMRI: the benefits of visual inspection - Lepping, Rebecca J.; Yeh, Hung-Wen; McPherson, Brent C.; Brucks, Morgan G.; Sabati, Mohammad; Karcher, Rainer T.; Brooks, William M.; Habiger, Joshua D.; Papa, Vlad B.; Martin, Laura E. (Frontiers in Neuroscience, 2023)
Background: Reliability of resting-state functional magnetic resonance imaging (rs-fMRI) can be improved by censoring or 'scrubbing' volumes affected by motion. While censoring preserves the integrity of participant-level data, including excessively censored data sets in group analyses may add noise. A variety of quality control (QC) approaches are employed to determine data quality and ultimately inclusion or exclusion of a fMRI data set in group analysis. In this paper, we describe our methods for performing QC of rs-fMRI data using software-generated quantitative and qualitative output and trained visual inspection. Results: The data provided for this QC paper had relatively low motion-censoring, thus quantitative QC resulted in no exclusions. Qualitative checks of the data resulted in limited exclusions due to potential incidental findings and failed pre-processing scripts. Conclusion: Visual inspection in addition to the review of quantitative QC metrics is an important component to ensure high quality and accuracy in rs-fMRI data analysis.